2011
DOI: 10.1038/cr.2011.100
|View full text |Cite
|
Sign up to set email alerts
|

Serum inducible kinase is a positive regulator of cortical dendrite development and is required for BDNF-promoted dendritic arborization

Abstract: Serum inducible kinase (SNK), also known as polo-like kinase 2 (PLK2), is a known regulator of mitosis, synaptogenesis and synaptic homeostasis. However, its role in early cortical development is unknown. Herein, we show that snk is expressed in the cortical plate from embryonic day 14, but not in the ventricular/subventricular zones (VZ/ SVZ), and SNK protein localizes to the soma and dendrites of cultured immature cortical neurons. Loss of SNK impaired dendritic but not axonal arborization in a dose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…30 SNK, can act as a polo-like kinase, when overexpressed can lead to abnormal branching into the significant process of the migrating cortical neurons in the electroporated cortices. 9 One study reported that glutamate stimulation could induce the activation of the SNK-SPAR pathway in cultured hippocampal neurons, resulting in a loss of mature dendritic spines. 11 In addition, a spleen-yin nourishing recipe-containing serum was also found having protective effects on neurons from the Abeta-induced neurotoxicity by blocking the SNK-SPAR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…30 SNK, can act as a polo-like kinase, when overexpressed can lead to abnormal branching into the significant process of the migrating cortical neurons in the electroporated cortices. 9 One study reported that glutamate stimulation could induce the activation of the SNK-SPAR pathway in cultured hippocampal neurons, resulting in a loss of mature dendritic spines. 11 In addition, a spleen-yin nourishing recipe-containing serum was also found having protective effects on neurons from the Abeta-induced neurotoxicity by blocking the SNK-SPAR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As such, MEK-ERK1/2 hyperactivity in the setting of TSC may promote dendritic hypertrophy via SRF-dependent transcriptional up-regulation of the FLNA gene. This is consistent with studies showing that MEK-ERK1/2 activity regulates neurite growth in many cell types ( e.g ., PC12 cells, many references) and dendritic growth in neurons (Collo et al, 2008; Guo et al, 2012; Ha and Redmond, 2008; Kim et al, 2004; Xu et al, 2014). Whatever the mechanism, our data showing that MEK1 overexpression leads to FLNA-dependent dendritic hypertrophy in wild type cells reinforces the finding that reduction of either MEK1 activity (using a dominant negative vector) or FLNA expression (using shRNA) normalizes dendritic hypertrophy in TSC.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK signaling has been shown to regulate the expression –at the transcriptional level‐ of serum inducible kinase (SNK, also known as Polo‐like kinase 2 PLK2). In this study, the authors showed that SNK is required for BDNF‐induced dendritic but not axonal growth [Guo et al, ].…”
Section: Signaling Pathways Underlying Bdnf‐induced Dendritic and Axomentioning
confidence: 99%